Return Migration as ‘Success’? : A Study on the Returned Migrants and Korean Language Institutes in Nepal - Seo, Seon-Young (남아시아연구, 2022)
Since Nepal and Korea signed a Memorandum of Understanding under the Employment Permit System (EPS) in 2007, the number of applicants for the Employment Permit System- Test of Proficiency in Korean (EPS-TOPIK) has increased every year. In the meantime, Korean language institutes, where prospective migrants study for the test, have become an attractive market for returnees who have acquired Korean language ability in Korea. This paper, based on the enthnographic fieldwork in Nepal, explores the reintegration strategies of these returnees via Korean language institutes in the face of structural hindrances that force many returnees to choose remigration to other countries. Analysing their engagement with Korean language institutes in Nepal, I highlight the agency they can exercise against becoming underclass workers in the global force of circular labour migration, but ironically contribute to the production of other working-class migrants and the institutionalised labour migration system in Korea. In this paper, I unpack such elements of circularity in labour migration between Nepal and Korea by investigating broader structures, regulatory migration regimes, and returnees’ survival strategies. KCI Citation Count: 0